Towards 45 watt single-cycle pulses from Yb:YAG thin-disk oscillators - Barbiero, Gaia; Ahmad, Raja N.; Wang, Haochuan; Köttig, Felix; Novoa, David; Tani, Francesco; Brons, Jonathan; Russell, Philip St. J.; Krausz, Ferenc; Fattahi, Hanieh (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Femtosecond and attosecond spectroscopy benefit directly from the availability of ultrashort, high-power lasers at megahertz (MHz) repetition rates. High repetition rates allow decreasing the measurement's acquisition time and enhancing signal to noise ratio. Moreover, efficient extension of the spectral bandwidth of high repetition rate sources to beyond one octave paves the way for novel broadband spectroscopy techniques, such as femtosecond fieldoscopy. Nowadays, ytterbium thin-disk oscillators and fiber lasers deliver 100-W-scale average power, at MHz repetition rates [1, 2]. However, their pulse duration is limited to hundreds of femtoseconds due to the narrowband emission cross-section of ytterbium, which can be overcomed by employing efficient, external spectral broadening schemes based on solid state materials [3] or gas filled hollow-core fibers [4,5]. In what follows we report on the external spectral broadening of 265 fs, 6 μJ pulses from a Yb:YAG thin-disk oscillator to 7fs (Fourier transform limit-FTL) in three nonlinear stages.
CRIS-Team Scopus Importer:2023-04-20